The influence of an Acute Pain Service on postoperative pain management in Jordan: a comparative case study - Al-Tawafsheh, Atef M.M. (2016)
Background and Aims: Acute pain services (APSs) have developed worldwide to improve the quality of postoperative pain management (POPM). Although there is evidence that APSs can reduce pain and side effects after surgery and improve nurses’ knowledge regarding pain management, the processes through which APSs influence these outcomes remains unclear. Previous studies regarding the influence of APSs on these outcomes have reported conflicting findings and there has been little research exploring clinicians’ perceptions of the APS, and POPM practice.